Constructing a New Triangular Trade Pattern - Feiteng ZHONG (East Asian Policy)
The overall development of Southeast Asia has been affected by the great power competition between China and the United States in recent years. Against the backdrop of ongoing trade frictions and the intensifying strategic competition between the two countries, Southeast Asia’s strategic position has become more prominent than ever. China recognises the need to not only build more stable and mutually beneficial trade relations, but also develop comprehensive economic relations with countries in the region. In this context, all parties should attempt to establish a new model of triangular trade relationship.